Extension of Meanings: Text and Image in Contemporary Chinese Photographic Works. (3rd July 2022) - He, Yining
Abstract: This essay focuses on an aspect of photographic practices that are often seen but seldom discussed in contemporary Chinese photography: the creative practices that focus on the relationship (e.g. complementarity and contrast) between text and image. Concerning the traditions of Chinese literati painting, contemporary semiotic theories from the West, and the development of narratologies, this essay examines the works of several contemporary photographic artists in China that combine text and image. More specifically, it focuses on the theoretical framework behind the diverse practices of the twenty-first century. It addresses three main topics: the traditions of Chinese literati painting (which includes poetry, calligraphy, painting, and seal carving), Roland Barthes' semiotic theory and its application in the visual world, and the theories and paradigms of storytelling in the evolution of narratology into its newer form. In addition, the essay explores how text and image theories and paradigms of different origins exist in contemporary art practices, as well as how they have extended the meanings of these works through the complementarity and conflict between text and image.